Large Physisorption Strain in Chemical Vapor Deposition of Graphene on Copper Substrates - He, Rui; Zhao, Liuyan; Petrone, Nicholas; Kim, Keun Soo; Roth, Michael; Hone, James; Kim, Philip; Pasupathy, Abhay; Pinczuk, Aron (Nano letters, 2012)
Graphene single layers grown by chemical vapor deposition on single crystal Cu substrates are subject to nonuniform physisorption strains that depend on the orientation of the Cu surface. The strains are revealed in Raman spectra and quantitatively interpreted by molecular dynamics (MD) simulations. An average compressive strain on the order of 0.5% is determined in graphene on Cu(111). In graphene on Cu (100), MD simulations interpret the observed highly nonuniform strains.